Pentingnya Profesionalisme Guru dalam Meningkatkan Kualitas Pendidikan - Syakdia Apria Ningsih (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, selfcontrol, personality, intelligence, noble morals, and the skills needed by themselves, society, nation and state. To realize the goals of education in Indonesia, one of the most important and very influencing factors is the professionalism of teachers in carrying out learning activities. Teachers must have competencies that include four important things, namely personal competence, professional competence, social competence and pedagogical competence. In this way, professional teachers can improve the quality of education by developing students' potential and creating a conducive learning atmosphere.